Pengaruh Pelayanan Kefarmasian di Rumah pada Pasien Diabetes Melitus Tipe 2 di Puskesmas Wilayah Kota Yogyakarta - Nur Rasdianah; Suwaldi Martodiharjo; Tri Murti Andayani; Lukman Hakim (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The increasing prevalence of diabetes mellitus (DM) in Indonesia requires participation of all parties including pharmacists. This study aims to determine the impact of the implementation of home pharmacy service guidelines for patients with type 2 diabetes mellitus on the level of knowledge, medication adherence, therapeurical satisfaction and glycemic control. This study used a quasi-experimental design with one group pre-test and post-test design involving 37 patients with type 2 diabetes mellitus who met the requirements of inclusion and exclusion criterias. The Diabetes Knowledge Questionnaire (DKQ-24) and the Diabetes Medication Satisfaction Tool (DMSAT) were used for collecting the data. Patient adherence was measured using a pillcount method and fasting blood sugar levels (FSB) data were obtained from the laboratory results. The study was conducted in two community health centers and patient’s home in the Yogyakarta Municipality area. The data were analysed using Wilcoxon and Spearman test. The results showed the change of the level of knowledge, medication adherence, therapeutic satisfaction and glycemic control before and after intervention of pharmacy services at home. The average decreasing of fasting blood sugar levels 17.09 mg/dL ± 1.43